ADDRESSING THE NEEDS OF ENGLISH LANGUAGE LEARNERS: STRATEGIES FOR ACADEMIC SUCCESS - Yuliasari, Ulfa; Usman, Usman (Transpublika Publisher, 2023)
This study aims to identify and understand the needs of English Language Learners (ELL) in elementary schools, as well as to explore effective teaching strategies to support their academic success. Using a qualitative approach with a case study method, data were collected through semi-structured interviews, classroom observations, and document analysis. The findings reveal that ELL students' needs encompass linguistic, cognitive, and affective aspects, requiring a holistic approach to learning. The study also highlights the critical role of teachers in creating an inclusive learning environment through differentiated instruction, the use of technology, and family engagement. However, challenges such as limited resources and inadequate teacher training pose barriers to the implementation of these strategies. The study concludes that comprehensive support from the educational environment is essential to help ELL students reach their academic potential. Recommendations for further research include exploring educational policies and more in-depth teacher training.